SPK Pemilihan Jurusan SNMPTN Menggunakan Metode SMART Berbasis Web di SMA Negeri 1 Lubuk Alung - Yessy Prima Putri; Defiariany Defiariany; Tri Aprianto Sundara (Journal of Science and Technology, 2022)
The Joint Selection for State University Entrance (SBMPTN) is a very important moment for prospective students to enter the world of lectures. This selection path is the biggest and most attractive opportunity for prospective students to be able to enter State Universities (PTN). SBMPTN is a selection route that is held openly and uses a written test-based selection. Prospective students need to prepare everything carefully to take part in the SBMPTN selection. When the SBMPTN registration was opened, the burden on the guidance and counseling teacher at SMA 1 Lubuk Alung became heavy because many students consulted the counseling teacher to provide input for students manually, namely comparing student grades with the majors of interest. For this reason, a Decision Support System (SPK) is needed to assist schools and BK teachers in determining the priority of majors on the SNMPTN pathway. DSS is used as an alternative in decision making, DSS utilizes data and models to solve unstructured problems, one of the models used in DSS is the Simple Multi Attribute Rating Technique (SMART). This method was chosen because of its simplicity in the calculation process so as to facilitate system development. This system is web-based so that students can access the web so they can choose their major. With this system, students are expected to be able to choose majors according to their wishes and abilities.